2019
DOI: 10.1097/tp.0000000000003056
|View full text |Cite
|
Sign up to set email alerts
|

Living Donor Liver Transplantation in Children: Perioperative Risk Factors and a Nomogram for Prediction of Survival

Abstract: Background. Living donor liver transplantation (LDLT) in children has achieved promising outcomes during the past few decades. However, it still poses various challenges. This study aimed to analyze perioperative risk factors for postoperative death in pediatric LDLT. Methods. We retrospectively analyzed medical records of pediatric patients who underwent LDLT surgery from January 1, 2014, to December 31, 2016, in our hospital. Predictors of mortality f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
4
7
0
Order By: Relevance
“…In our study, a cut-off point of more than 3 mmol/L in the immediate post-operative period (first hour after admission to the PICU) was related to biliary complications, vascular thrombosis and death. In adult patients, Jipa et al found a similar cut-off point to what was found in our study (>3 mmol/L), which was correlated with intraoperative blood loss when evaluated in the immediate post-operative period ( 27 , 28 ).…”
Section: Discussionsupporting
confidence: 89%
“…In our study, a cut-off point of more than 3 mmol/L in the immediate post-operative period (first hour after admission to the PICU) was related to biliary complications, vascular thrombosis and death. In adult patients, Jipa et al found a similar cut-off point to what was found in our study (>3 mmol/L), which was correlated with intraoperative blood loss when evaluated in the immediate post-operative period ( 27 , 28 ).…”
Section: Discussionsupporting
confidence: 89%
“…Higher PELD/MELD scores had a trend towards significant correlation with poor patient survival in our work, also, a higher PELD score was an independent predictor of poor patient survival in Pan et al, 2020 [ 22 ], Lu, et al, 2020 [ 25 ] and Kehar et al, 2019 [ 32 ] studies , moreover, it was a significant predictor of patient loss in Oh et al, 2010 [ 42 ]; study, in contrast, it did not affect survival in Kitajima et al, 2017 [ 2 ], Raices, et al, 2019 [ 8 ], Chung, et al, 2020 [ 48 ] or Shehata et al, 2012 [ 58 ] studies.…”
Section: Discussionsupporting
confidence: 71%
“…They should be prevented, and if occurred; should be diagnosed and managed early to improve graft and patient outcomes, however, those outcomes are affected also by additional variables (i.e. Large for size graft (LFSG), pediatric end-stage liver disease (PELD)/model for end-stage liver disease (MELD) scores, centre experience/volume, operative time, operative blood loss, blood transfusion units, etc); those variables should be modulated also for getting better short-and long-term outcomes [ 8 , [22] , [23] , [24] , [25] , [26] ] .…”
Section: Introductionmentioning
confidence: 99%
“…In a similar study from Kyoto, Ueda et al ( 17 ) reported the results in 568 primary LDLTs and showed that the factors independently associated with worse patient survival were fulminant liver failure, GRWR <0.8%, and ABO incompatibility, but the analysis was not limited to 90‐day survival. A recent study from Lu et al ( 18 ) on 430 primary PLDLTs found that PELD score, neutrophil lymphocyte ratio, GRWR (>4%), and intraoperative use of norepinephrine were independent prognostic factors related to 180‐day patient survival. In this article, the majority of the recipient’s deaths occurred within 6 months after transplant (36/37), but the follow‐up time in the series was relatively short.…”
Section: Discussionmentioning
confidence: 99%